Efektivitas Program Reklamasi Pasca Tambang Timah di Kecamatan Merawang Kabupaten Bangka - Sari, Dian Permata; Buchori, Imam (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
According to the Law No. 32 in 2004 on Regional Government and Law No. 4 of The Coal and mineral mining, the governments have rights to take policy relating to areas of tin ore mining PT Timah Tbk, as a state-owned company (BUMN) engaged in tin mining in the Bangka Belitung Province, must implement the post mining reclamation program in the former tin mining operations. Merawang subdistrict is one of the operational area of tin mining in Bangka Belitung Province, which effort by PT Timah Tbk. This research used techniques ofÂ  descriptive and quantitative analyze. the level of effectiveness was ineffective and most ineffective. External and internal factors influence effectiveness program still so far is calledÂ  effective.